Regenerating the kidney using human pluripotent stem cells and renal progenitors. (3rd July 2018) - Becherucci, Francesca; Mazzinghi, Benedetta; Allinovi, Marco; Angelotti, Maria Lucia; Romagnani, Paola
ABSTRACT: Introduction : Chronic kidney disease is a major health-care problem worldwide and its cost is becoming no longer affordable. Indeed, restoring damaged renal structures or building a new kidney represents an ambitious and ideal alternative to renal replacement therapy. Streams of research have explored the possible application of pluripotent stem cells (SCs) (embryonic SCs and induced pluripotent SCs) in different strategies aimed at regenerate functioning nephrons and at understanding the mechanisms of kidney regeneration. Areas covered : In this review, we will focus on the main potential applications of human pluripotent SCs to kidney regeneration, including those leading to rebuilding new kidneys or part of them (organoids, scaffolds, biological microdevices) as well as those aimed at understanding the pathophysiological mechanisms of renal disease and regenerative processes (modeling of kidney disease, genome editing). Moreover, we will discuss the role of endogenous renal progenitors cells in order to understand and promote kidney regeneration, as an attractive alternative to pluripotent SCs. Expert opinion : Opportunities and pitfalls of all these strategies will be underlined, finally leading to the conclusion that a deeper knowledge of the biology of pluripotent SCs is mandatory, in order to allow us to hypothesize their clinical application.